Mutants of Staphylococcus aureus with Increased Sensitivity to Ultraviolet Radiation - Goering, R. V. (1971)
Nitrosoguanidine (NG) mutagenesis of Staphylococcus aureus resulted in the isolation of eight mutants exhibiting 3 to 28 times greater sensitivity to ultraviolet (UV) radiation. These mutants were further characterized by their ability to repair UV-irradiated bacteriophage, to act as recipients in the transduction of antibiotic resistance, and their sensitivity to NG. Based on the available data, six of these mutants are reduced in their ability to perform host-cell reactivation. One of the remaining two mutants may be deficient in post-replication repair.